Alkaloids isolated from the bark of Alseodaphne Peduncularis (Wall.Ex Nees) MEISN and the roots of Alseodaphne Corneri Kosterm (IR) - Siti Nor Fadzilah Mohamad (2014)
The objectives of this study are to extract and isolate the alkaloids from two species of Alseodaphne; Alseodaphne peduncularis (Wall. ex Nees) Meisn from Kluang- Mersing, Johor and Alseodaphne corneri Kosterm from University Malaya, Kuala Lumpur. The extraction process of the plant material started by cold percolation process using hexane to remove non-polar organic compounds, waxes and fats. The plant material then re-extracted by dichloromethane using soxhlet extractor followed by acid-base extraction to get the alkaloid crude extract. The isolation and purification of alkaloids from the crude extract were done by using various chromatographic techniques including column chromatography and preparative thin layer chromatography. The elucidation of the isolated alkaloids were determine by using various spectroscopic methods such as 1D NMR (1H, 13C and DEPT) and 2D NMR (COSY, HMQC and HMBC), ultraviolet (UV), infrared (IR) and mass spectrometry (MS). The structures were further confirmed by comparison with other literature data. Isolation and purification of alkaloids from the bark of Alseodaphne peduncularis (KL 5165) yielded four aporphines; boldine 69, norpredicentrine 90, norlirioferine 91 and norboldine 78. In addition, seven alkaloids were successfully isolated from the roots of Alseodaphne corneri (KL 4928). The isolated alkaloids include two aporphines; laetanine 30, boldine 69 and five bisbenzylisoquinolines; gyrolidine 47, stephasubine 92, 2-norobaberine 93, 3,4-dihydrostephasubine 94 and O-methyllimacusine 95. The bioactivity study on the bark crude extract of Alseodaphne peduncularis and three isolated aporphines; boldine 69, norlirioferine 91 and norboldine 78 showed good to moderate antiplasmodial activity against Plasmodium falciparum after compared to the standard (chloroquine; 0.087 g/ml) with IC50 value of 2.135, 1.067, 2.786 and 2.228 g/ml, respectively. It was found that boldine 69 showed the most potent activity with an IC50 value of 1.067 g/ml and it showed potential for antiplasmodial drug. The extraction and isolation of alkaloids from this species will be continued to determine various type of alkaloids contents and new alkaloids findings. Moreover, the isolated alkaloids should be tested with other biactivity test such as cytotoxicity, antibacterial and antifungal activities for new drugs discovery.